2017
DOI: 10.5194/wes-2017-38
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Wind Turbine Component Loads Under Yaw-Offset Conditions

Abstract: Abstract. Renewed interest in yaw control for wind turbine and power plants for wake redirection and load mitigation demands a clear understanding of the effects of running with skewed inflow. In this paper, we investigate the physics of yawed operations, building up the complexity from a simplified analytical treatment to more complex aeroelastic simulations. Results in terms of damage equivalent loads (DELs) and extreme loads under operating, misaligned conditions are compared to data collected from an instr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…To estimate the yaw position uncertainty, we compared operational data from an NREL turbine with a nearby meteorological measuring mast (NWTC Information Portal, 2019); these data were examined previously by Fleming et al (2018), Annoni et al (2018), and Damiani et al (2018). In the present study, the wind direction recorded at the turbine was compared to the wind direction measured on the upstream meteorological mast.…”
Section: Uncertainty Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the yaw position uncertainty, we compared operational data from an NREL turbine with a nearby meteorological measuring mast (NWTC Information Portal, 2019); these data were examined previously by Fleming et al (2018), Annoni et al (2018), and Damiani et al (2018). In the present study, the wind direction recorded at the turbine was compared to the wind direction measured on the upstream meteorological mast.…”
Section: Uncertainty Estimatesmentioning
confidence: 99%
“…Based on the shape of the distribution in Figure 2, we parameterize the yaw misalignment as a two-sided exponential distribution, termed the Laplace distribution, given by Figure 2. Errors in the yaw position y y y for a test turbine at the National Wind Technology Center at NREL (Fleming et al, 2018;Annoni et al, 2018;Damiani et al, 2018). The solid blue and green lines show Laplace and Gaussian distributions, respectively.…”
Section: Uncertainty Estimatesmentioning
confidence: 99%
“…When superimposing an additional low-velocity zone, tower shadow or shear for example, the yaw-symmetry is disturbed. Asymmetric load distributions for turbines exposed to sheared inflow were recently reported by Damiani et al (2017). They showed that vertical wind shear causes asymmetric distributions of angle of attack and relative flow velocity in the course of a blade revolution.…”
mentioning
confidence: 97%
“…The so-called Mexnext project revealed modeling deficiencies while shedding light on complex unsteady flow 5 phenomena during yaw. In a recent paper by Damiani et al (2017) damage equivalent loads and extreme loads under yaw misalignment are measured and predicted for a fully instrumented wind turbine. They observed rather complex, inflow-dependent load distributions for yaw angle offsets.…”
mentioning
confidence: 99%
“…Likewise the wind speed component perpendicular to the rotor is also decreases by a cosine relation and with the wind speed having a cubic impact on power a cosine³-relationship is more dominant for smaller angles (Burton et al, 2001 andMamidipudi et al, 2011). In addition to power losses, yaw errors are also increasing turbine loads (Wan et al, 2015 andDamiani et al, 2017). 10…”
mentioning
confidence: 99%